Functional state of peripheral nerves of lower limbs in patients with deforming knee joint arthrosis - T. K. Verkhozina; E. G. Ippolitova; N. I. Arsentieva; E. S. Tsyslyak (Acta Biomedica Scientifica)
With osteochondrosis of the lumbar spine and L3, L4 lesions, local overloads of the spinal-motor segment lead to disruption of the functioning of the biokinematic chain "spine-lower limbs". Gonarthrosis is considered as an independent disease requiring surgical treatment. We have not found on the functional state of the peripheral neuromotor apparatus, with taking into account segmental radicular manifestations in patients with grade 3-4 gonarthrosis. We examined the tibial and peroneal nerves, and H-reflex in 51 patients undergoing treatment at the clinical department of traumatology and orthopedics of ISCST In all examined patients we revealed changes in the function of the peripheral nerves of the lower limbs (increase in the threshold values of the M-response to 24.8 mA (norm - 16 mA), a decrease in the direct muscle response amplitude to an average of 0.6 mV (norm - 2.0 mV), a decrease in the rate impulse up to 37-39 m/s (norm - 40 m/s), all changed were more pronounced on the affected limb. The revealed changes in ENMG indices could be due to both degenerative changes in periarticular tissues and radicular syndrome in lumbar osteochondrosis. Changes in reflex excitability were observed in combination with prolapse of the H-reflex in the majority of patients. The data obtained indicate damage to the roots and spinal motoneurons in L3-L4-L5 and a change in the functional state of the peripheral nerves of the lower limbs, indicating a single pathogenetic mechanism of degenerative processes in the knee and spine.